2022
DOI: 10.1111/avj.13166
|View full text |Cite
|
Sign up to set email alerts
|

Feline immunodeficiency virus (FIV) infection in domestic pet cats in Australia and New Zealand: Guidelines for diagnosis, prevention and management

Abstract: Despite the passage of over 30 years since its discovery, the importance of feline immunodeficiency virus (FIV) on the health and longevity of infected domestic cats is hotly debated amongst feline experts. Notwithstanding the absence of good quality information, Australian and New Zealand (NZ) veterinarians should aim to minimise the exposure of cats to FIV. The most reliable way to achieve this goal is to recommend that all pet cats are kept exclusively indoors, or with secure outdoor access (e.g., cat enclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 99 publications
0
14
1
Order By: Relevance
“…It was also available in North America from 2003 to 2017, but has never been commercially available in Europe. Every jurisdiction should perform its own testing to determine the accuracy of any FIV PoC test kit, including v-RetroFel ® FIV, prior to adopting them for use [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also available in North America from 2003 to 2017, but has never been commercially available in Europe. Every jurisdiction should perform its own testing to determine the accuracy of any FIV PoC test kit, including v-RetroFel ® FIV, prior to adopting them for use [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity of FIV RealPCR ® testing under Australian conditions were reported to be 92% and 99% [ 60 ]. Virus isolation was used to confirm FIV infection in the two FIV-vaccinated cats at the University of Florida and the University of Glasgow [ 60 , 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…In some cases, residual EDTA blood was sent refrigerated for FIV molecular testing at a commercial laboratory (FIV RealPCR TM , IDEXX Laboratories, Brisbane, Queensland, Australia). FIV RealPCR TM testing detects proviral DNA (FIV DNA inserted into the cat’s genome), as well as viral RNA, due to a reverse-transcriptase (RT) step that is performed as part of the PCR assay [ 49 ]. FIV RealPCR TM is reported to have sensitivity and specificity of 92% and 99% in a population of FIV-vaccinated and FIV-unvaccinated cats in Australia [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…This vaccine remains available in Japan, Australia and New Zealand. Although efficacy of this vaccine against experimental, heterologous FIV challenge has been shown, there has long been debate about whether it can effectively cross‐protect against the many different subtypes of FIV found in different geographical areas (Beczkowski et al., 2015; Coleman et al., 2014; Dunham et al., 2006; Hosie et al., 1995; Stickney et al., 2020; Westman et al., 2022; Yamamoto et al., 2007). Experimental studies have shown conflicting results, some showing strong protection afforded by this vaccine and others showing absence of protection.…”
Section: Feline Vaccination Guidelinesmentioning
confidence: 99%
“…Until recently, use of this FIV vaccine complicated diagnosis of FIV infection. Vaccination leads to the production of antibodies, presence of which is typically used to make a diagnosis of FIV infection (Westman et al., 2022). Fortunately, there are commercially available, in‐practice antibody detection test kits that can discriminate between FIV infected and uninfected cats, so long as testing is not done soon after vaccination (Westman et al., 2017).…”
Section: Feline Vaccination Guidelinesmentioning
confidence: 99%